2012
DOI: 10.1075/japc.22.1.03bur
|View full text |Cite
|
Sign up to set email alerts
|

The marginalized positions of Thai professional writers on the global hegemony of English

Abstract: This qualitative study investigated the positions of the Thai professional writers towards Thai English. Data was collected from in-depth interviews of 20 Thai bilingual writers. The findings revealed that most of the writers had different ways to distant themselves from Thai English. The majority of the participants expressed a marginalized view toward their English. Their attitudes were greatly influenced by the hegemonic Standard English. Evidently, Thai perceptions of the English language conformed to a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The language playfulness encouraged in this kind of creative writing space attracts more readers who share common experiences of "life in several languages" (Kramsch, 2006). In the case of Thai English writers, Buripakdi (2012) found that creative manipulation of the English language empowered writers, strengthened emotional attachment to the language, and consequently, weakened hegemonic linguistic practices and oppression.…”
Section: Trends In Esl/efl Writing Instructionmentioning
confidence: 98%
“…The language playfulness encouraged in this kind of creative writing space attracts more readers who share common experiences of "life in several languages" (Kramsch, 2006). In the case of Thai English writers, Buripakdi (2012) found that creative manipulation of the English language empowered writers, strengthened emotional attachment to the language, and consequently, weakened hegemonic linguistic practices and oppression.…”
Section: Trends In Esl/efl Writing Instructionmentioning
confidence: 98%
“…Research has shown how speakers brand their own speech variety as inferior in a myriad of other linguistic communities across a variety of different nations (Martinez & Petrucci, 2004;Owens & Baker, 1984), and sometimes even across different times in the same nation (Preston, 2013). More recently, research has also shown how speakers of the 'inferior' language variety are typically 'non-native' speakers of the language (Buripakdi, 2012;Cho, 2015). Similarly, the concept of linguistic ownership or the lack thereof, has seen some intellectual debate, particularly in the very nature of linguistic ownership itself (Bokhorst-Heng, Alsagoff, McKay, & Rubdy, 2007;Norton, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Given that English has come to be spoken by billions of international speakers in non-native settings, it has ceased to be the sole property of people with particular ethnic backgrounds or tied up with particular inner-circle communities (Widdowson, 1994(Widdowson, , 1997. Thus, the deeply rooted ELT assumption claiming that 'standard English', the model that language learners should aspire for, should be informed by native speakers (Buripakdi, 2012a(Buripakdi, , 2012bJindapitak & Teo, 2011 seems to be less supported and unrealistic. This is because we now live in the globalized era where people speak Englishes rather than English, those using the language in order to communicate with international speakers.…”
Section: Introduction and Contextualizationmentioning
confidence: 99%
“…They held the belief that everything associated with the West was more standardized, advanced and sophisticated. Buripakdi (2012b) concluded that the belief of this kind reaffirmed that the writers devalued their own version of English, had low self-esteem, and even marginalized their own discourse. Similarly, Methitham (2009) Regarding linguistic and cultural dimension, the teacher participants believed that Thai students will learn English better if they conform to the linguistic and cultural norms of native speakers.…”
Section: Introduction and Contextualizationmentioning
confidence: 99%
See 1 more Smart Citation